Medically unexplained oropharyngeal dysphagia (MUNOD): a case report - Md Aris, Mohd Aznan; Wan Mansor, Wan Najwa Aima (UniKL Royal College of Medicine Perak (UniKL RCMP), 2023)
This is a case of an uncommon presentation for a common diagnosis. We wanted to highlight the diagnostic dilemma of medically unexplained oropharyngeal dysphagia (MUNOD) when the patient presented with dysphagia with normal anatomy and swallowing function. The core problem of the patient is psychiatric illness, but the main complaint is somatic symptom. Major depression is rarely present with dysphagia as the chief complaint, and medical practitioner may consider psychiatric illness as a differential diagnosis for dysphagia.